2022
DOI: 10.31557/apjcc.2022.7.2.285-293
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Predicting Chemotherapy-induced Severe Neutropenia and Outcome in Advanced Stage Non-small Cell Lung Cancer: Data from the Limited Resource in Thailand

Abstract: Introduction: Chemotherapy-induced severe neutropenia requires dose reduction, delay in treatment, or discontinuation, and induces neutropenic complications resulting in poor outcomes and increased healthcare costs. This study aims to identify the risk factors for chemotherapy-induced severe neutropenia and outcome in advanced-stage NSCLC. Method: From July 2014-January 2019, advanced-stage NSCLC who received chemotherapy were retrospectively analyzed. Demographic and risk factors data were collected from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
1
0
0
Order By: Relevance
“…Although the incidence of chemotherapy- related adverse events differed significantly between the two groups, this did not significantly affect OS. This is consistent with a recent retrospective study from a resource-limited region of Thailand (Neesanun, 2022), which demonstrated that chemotherapy-related adverse events (e.g., severe neutropenia) were not associated with treatment and survival outcomes, including the response rate, progression-free survival, and OS. Even though the CG regimen provided a higher rate of chemotherapy-related adverse events, patients in this group tended to achieve more complete cycles of chemotherapy than those in the PC group.…”
Section: Discussionsupporting
confidence: 91%
“…Although the incidence of chemotherapy- related adverse events differed significantly between the two groups, this did not significantly affect OS. This is consistent with a recent retrospective study from a resource-limited region of Thailand (Neesanun, 2022), which demonstrated that chemotherapy-related adverse events (e.g., severe neutropenia) were not associated with treatment and survival outcomes, including the response rate, progression-free survival, and OS. Even though the CG regimen provided a higher rate of chemotherapy-related adverse events, patients in this group tended to achieve more complete cycles of chemotherapy than those in the PC group.…”
Section: Discussionsupporting
confidence: 91%